A Comparative Study of Chinese-Thai Speech Act of Request: A Case Study of Campus Scenarios : 汉泰请求言语行为对比研究——以校园情景为例 - Sapermsup, Noramon (Published by Confucius Institute UNS, 2024)
A request is a common speech act in any language and is essential for successful communication. The study aims to compare the Chinese and Thai speech act of request in the campus scenario. Using the oral discourse completion test method, it examines the characteristics of request speech acts among 20 native Chinese speakers and 20 native Thai speakers. It focuses on analyzing the use of the initial action language in the request speech act, and the use of internal and external modifiers in the central action language. According to the research, it was found that although these two languages had some similarities in the implementation of the speech act of request, there were differences in many aspects and both had their own characteristics. This study argued that this difference was closely related to the Chinese and Thai socio-cultural characteristics.